Non-destructive methods for mango ripening prediction: Visible and near[1]infrared spectroscopy (visNIRS) and laser Doppler vibrometry (LDV): Data - Alamar, M. Carmen; O'Brien, Ciara; Falagán, Natalia; Landahl, Sandra; Terry, Leon A.; Kourmpetli, Sofia (Cranfield University, 2024)
This data set includes reference measurements (firmness, colour [lightness, chroma and hue angle], total soluble solids [TSS], individual sugar concentrations [glucose, fructose, sucrose]), as well as visible and near-infrared spectroscopic (vis-NIRS) data (nm) and resonant frequency measured by laser Doppler vibroemetry (LDV) on 'Keitt' and 'Kent' mango fruit.
Keywords: Mangifera indica'; 'Firmness'; 'Food loss'; 'chemometrics methods'; 'resonant frequency'; 'postharvest'